Increasing stair use in an office worksite through an interactive environmental intervention - Swenson, Theadora; Siegel, Michael (American journal of health promotion, 2013)
Examine the effects of an interactive environmental intervention on stair usage. A nonrandomized, quasi-experimental intervention. Two three-story office buildings. Approximately 200 employees at the intervention site and 140 at the comparison site. The stairwell was decorated with interactive paintings such as maps, storyboards, and wish lists to encourage employees to take the stairs rather than the elevator. Daily stair and elevator usage were measured using electronic sensors or door-access card counters for 2 weeks prior to the intervention and 6 weeks after. The daily counts of stair use were modeled using a Poisson regression to estimate the effect of the intervention on staircase use. At baseline, the mean proportion of stair use relative to stair plus elevator use at the intervention site was 31.5% (95% confidence interval [CI], 30.3%-32.7%). During the 6-week intervention period, this proportion increased significantly to 66.2% (95% CI, 64.4%-67.9%). There was no significant change in stair use at the comparison site. In a Poisson regression of the daily number of stair users, the incidence rate ratio associated with the intervention was 2.57 (95% CI, 2.35-2.82). This interactive environmental intervention increased stair usage in an office setting relative to the comparison site, and this increase was sustained over a 6-week period. Adding interactive components to motivational or environmental change interventions shows promise in increasing stair usage.